Penerapan Comsoal terhadap Peningkatan Effisiensi Kerja pada Lintasan Produksi - Riska Tri Prasyawati (Department Industrial Engineering, University of Muhammadiyah Malang, 2008)
Company of Weighing-Machine Merk of SIMA represent company which producing various weighing-machine type with production the core important weighing-mechine of sentisimal 300 kg, 500 kg, 1000 kg, Desk weighing-mechine and pendulum weighing-mechine. This company also serve order from various company of a kind as according to request. To overcome the problems conducted by repairing of trajectory produce with line of balancing with method of COMSOAL at Q.S software version 3.0. Planning of trajectory balance with this COMSOAL aimed to get minimum Delay Balance and also improve Line of efficiency, so that with this situation will be got by the make-up of productivity. In the plan repeat lini produce with approach method of COMSOAL this is got by the amount of Work Station: 7, Efficiency: 47,05%, Production output: 12 unit/mont, Degradation of Balance Delay and Cost saving per product unit Rp105.289,00. Become with planning repeat line produce with of line balancing method of COMSOAL hence got the growingof efficiency, so that production proses walk more fluent and all request earn full filed.